ANALISIS FAKTOR YANG MEMPENGARUHI RETURN SAHAM DALAM ISSI SEKTOR CONSUMER GOODS INDUSTRY - Sevie Musri; Inggritia Safitri M; Nurul Huda (Media Ekonomi, 2020)
This research is intended to determine the effect of Asset, Current Ratio, Debt Equity Ratio, Net Profit Margin, Return On Asset, Asset Turnover Ratio on sharia stock return on Sharia Indonesia Stock Exchange (Index Saham Syariah Indonesia). This research was conducted using quantitative approach with the object of research on the company at the Sharia Indonesia Stock Exchange registered in the periode 2018, with a total of 40 companies. The data collection technique uses purposive sampling. The data analysis technique used in answering the hypothesis of this study is linear regresion analysis with dummy variable and numeric variables. The result of this study indicate that partially net profit margin and return on asset have a significant effect on sharia stock return in the Sharia Indonesia Stock Exchange. Simultaneous asset, current ratio, debt equity ratio, net profit margin, return on asset, asset turnover ratio have a significant effect on sharia stock return in the Sharia Indonesia Stock Exchange.